PENGEMBANGAN PERANGKAT PEMBELAJARAN AKUNTANSI DENGAN MENGGUNAKAN PENDEKATAN SAINTIFIK - Nanditia Widiasmara; Lilik Sri Hariani; Affan Afian (Jurnal Riset Pendidikan Ekonomi, 2018)
This research is a research development of accounting learning tools in adjusting journal material to financial statements. The purpose of this study is to produce learning tools that can be used to support learning activities. The steps applied in this study include: (1) Identification of Potential and Problems; (2) Data Collection; (3) Product Design; (4) Design Validation; (5) Design Revision; (6) Product Trial; (7) Product Revision; and (8) Usage Trial. The subjects of this study were class X students at SMK PGRI 6 Malang, totaling 15 students. Data collection techniques in this study used observation, interviews, and questionnaires. The results of the validation of the learning tools that have been carried out by experts obtain feasible and effective criteria to be applied. The implication of this research development in accounting learning tools is that students become more active in learning activities because learning activities are more student-center.